2017
DOI: 10.1111/are.13551
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of geographic origin, salinity and feed on stable isotope profile of Pacific white shrimp (Litopenaeus vannamei )

Abstract: Increasing numbers of mislabelled seafood products in the globalized market underline the need for approaches to identify the origin of these products. Pacific white shrimp cultured in different salinities (Litopenaeus vannamei) from 16 locations in China and USA were collected and differentiated based on d 13 C and d 15 N values. The d 13 C and d 15 N values of 16 commercial feeds used in shrimp culture were measured and effects of feed on C and N stable isotope composition in shrimp were investigated. Carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…During shrimp culture, the farmers may use several brands of commercial feeds with different ingredients and isotopic signatures. Li et al [156] reported that the δ 13 C and δ 15 N values in 16 commercial feeds used in shrimp culture in China ranged from −23.03 to −24.75% , and from 2.1 to 8.18% , respectively. The dietary shifts could influence the stable isotope signature of shrimp.…”
Section: Isotopic Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…During shrimp culture, the farmers may use several brands of commercial feeds with different ingredients and isotopic signatures. Li et al [156] reported that the δ 13 C and δ 15 N values in 16 commercial feeds used in shrimp culture in China ranged from −23.03 to −24.75% , and from 2.1 to 8.18% , respectively. The dietary shifts could influence the stable isotope signature of shrimp.…”
Section: Isotopic Techniquementioning
confidence: 99%
“…Compared with the marine ecosystem, the freshwater ecosystem generally has low δ 13 C and δ 15 N values [159,161]. Previous studies reported different δ 13 C and δ 15 N values in shrimp and fish cultured in freshwater and seawater [156,159]. Hence, all of these factors should be compared when using isotopic traceability methods to allow for deter animal origin product fraud.…”
Section: Isotopic Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Organismos cultivados são influenciados por diferentes regimes alimentares e ambientes em comparação com organismos pescados no habitat natural. Essas diferenças levam às composições isotópicas distintas e, consequentemente, a rastreabilidade dos produtos (ARECHAVALA-LOPEZ et al, 2013;VINCI et al, 2013;GAMBOA-DELGADO et al, 2014;LI et al, 2018;FERREIRA et al, 2021). Os isótopos estáveis comumente utilizados na autenticação e rastreabilidade são 13 C/ 12 C, 18 O/ 16 O, 2 H/ 1 H, 15 N/ 14 N e 34 S/ 32 S, 11 B/ 10 B e 87 Sr/ 86 Sr (LI et al, 2016).…”
Section: Abordagem Temática Descriçãounclassified
“…A técnica de isótopos estáveis tem potencial no fornecimento de informações da exploração pesqueira de decápodes, e pode servir como ferramenta para avaliar os impactos nas espécies exploradas (e.g. JACKSON et al, 2012;GAMBOA-DELGADO et al, 2014;MAZUMDER et al, 2015;ORTEA e GALHARDO et al, 2015;FRY et al, 2016;GORMAN et al, 2017;HINZ et al, 2017;LI et al, 2018;GOPI et al, 2019;MARTÍNEZ-DURAZO et al, 2019;GÜL & GRIFTEN et al, 2020;TAO et al, 2020;YORIO et al, 2020;FERREIRA et al, 2021). Entretanto, esses estudos ainda não representam percentual elevado das abordagens realizadas na última década (Figura 3).…”
Section: Abordagem Temática Descriçãounclassified